Design ideas of the top layer of the mine Internet of things - Enjie DING; Qingsong HU (物联网学报)
The flourishing development of the mine network requires the technology of the mine Internet of things from the top layer.The top layer design mine networking technology completed in 2017 by the State Administration of Production Safety Supervision was read.From the aspects of the design ideas,development status,challenges,strategic objectives,the key technology and implementation route and security needed,the technical background and core contents of top layer design were analyzed.It will provide some references for researchers and technology managers in mining industry to read,understand and use “top layer design”.